'Between a whisper and a shout': repealing the eighth and pro-choice Irish women's abortion testimonies. Issue 2 (26th January 2022) - Ralph, David
Abstract: In this paper I analyse the written testimonies submitted by pro-choice Irish women to the government in advance of the Referendum to Repeal the Eighth Amendment in May 2018. These testimonies are all in favour of legal reform to allow abortion access. However, the women's narratives are far from homogeneous in how they view abortion and how they present their abortion histories. Some offer a categorically pro-choice position with unapologetic calls for the liberatory potential of abortion in society to be recognized. Others, however, are far more cautious, far more conciliatory. Here, drawing on a powerful set of normative expectations around femininity, sexuality, class and family, such pro-choice women invoke a particular cultural meaning of abortion that, paradoxically perhaps, calls for the end to prohibitions on abortion while simultaneously provoking certain anti-abortion sentiments in detailing their individual abortion histories. I also suggest that adopting a defensive, almost apologetic endorsement of abortion may have significant anti-abortion side-effects in restricting future access to reproductive rights. Instead, what is called for, from a pro-choice advocacy perspective, is developing a culture of outspokenness around abortion to counter further anti-abortion inroads into women's reproductive lives.